Review on the enantioselective separation and environmental determination of chiral contaminates - LU Hang; MA Yun; LIU Hui-jun; LIU wei-ping (浙江大学学报. 农业与生命科学版, 2002)
Approaches to the chromatographic (GC, HPLC, CE, SFC and TLC) enantiomer separation and determination of chiral contaminates are reviewed. The enanriomers of chiral contaminates are selectively degradation and interaction in soil and water environment. For the separation and determination of main type chiral pesticides, the paper gives in more detail introduction.